STUDY OF SALINITY INTRUSION AT BERAU DELTA, EAST KALIMANTAN, INDONESIA USING ANALITICAL METHOD - Rahmatulloh, Risqi
This study intends to determine the salt intrusion that occurred in Berau Delta using observational data analysis and to approach Savenije analytical models (spreadsheets). Intrusion data is divided into 5 different times namely May 16th, June 20th, 2nd, 15th and September 20th, 2007. From the results of observational data obtained the shortest intrusion occurred on May 16 compared to others with a value of 5 psu at the point of 34 km from the starting point of data retrieval. For June 20 the value of 5 psu is at the point of 56 km. 5 psu value on September 2, 2007 was at the point of 64 km. The value is at the point of 58 km on September 15, 2007. For September 20, 2007 the value is at the point of 60 km. The variation in intrusion that occurs is caused by the balance between river discharge and tides that occur as a dominant factors. On May 16, 2007 the flow of river discharge of 660 m3/s with a tidal current of 0,8 m /s resulted in a salinity curve that was closer to the estuary mouth and on September 2 had a more shifted curve towards the headwaters which was marked by a high salinity value of 20 psu in the Berau River. That can happen because the value of river discharge at that time tends to be small at 443 m3/s and tidal currents of 0.8 m/s. Based on the value of estuarine number, Berau Estuary is included in the form of bell or trumpet estuary (bell shape estuary). From the Canter-Cremers and Richardson number, Berau Estuary is included in the partially mixed estuary category with an N value above 0.1 and NR value above 0,08. The level of compatibility of the analytical model used can be said to be good with an average correlation coefficient value greater than 90%.